2006
DOI: 10.1128/ec.00158-06
|View full text |Cite
|
Sign up to set email alerts
|

Cch1 Mediates Calcium Entry in Cryptococcus neoformans and Is Essential in Low-Calcium Environments

Abstract: The ability of Cryptococcus neoformans to grow at the mammalian body temperature (37°C to 39°C) is a well-established virulence factor. Growth of C. neoformans at this physiological temperature requires calcineurin, a Ca 2؉ /calmodulin-dependent protein phosphatase. When cytosolic calcium concentrations are low (ϳ50 to 100 nM), calcineurin is inactive and becomes active only when cytosolic calcium concentrations rise (ϳ1 to 10 M) through the activation of calcium channels. In this study we analyzed the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
95
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 50 publications
13
95
0
1
Order By: Relevance
“…Moreover, hypha formation and maintenance defects, as well as sensitivity to oxidant agents, were identified in the mutant strains, which demonstrates that CCH1 and MID1 play important roles in morphogenesis, the oxidative stress response, and virulence in Candida albicans (86,87). CCH1 also plays a role in mediating the virulence of C. neoformans and is required for the growth of C. neoformans at low extracellular Ca 2ϩ concentrations, especially at mammalian body temperatures (45). In aspergilli, the homologs of CCH1 and MID1, cchA and midA, not only have the functional benefits of fast growth but also play important roles in calcium homeostasis and virulence (50,51).…”
Section: The Roles Of Calcium Signaling In Fungal Cell Survivalmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, hypha formation and maintenance defects, as well as sensitivity to oxidant agents, were identified in the mutant strains, which demonstrates that CCH1 and MID1 play important roles in morphogenesis, the oxidative stress response, and virulence in Candida albicans (86,87). CCH1 also plays a role in mediating the virulence of C. neoformans and is required for the growth of C. neoformans at low extracellular Ca 2ϩ concentrations, especially at mammalian body temperatures (45). In aspergilli, the homologs of CCH1 and MID1, cchA and midA, not only have the functional benefits of fast growth but also play important roles in calcium homeostasis and virulence (50,51).…”
Section: The Roles Of Calcium Signaling In Fungal Cell Survivalmentioning
confidence: 97%
“…The major calcium influx system components CCH1 and MID1 have been identified as important factors in the survival of many fungi (45,48,50,87). Previous reports have demonstrated that CCH1 and MID1 are responsible for the resistance of Candida albicans to azoles, as the deletion of the CCH1 and MID1 genes attenuated the strain's resistance to fluconazole and itraconazole, and the cch1⌬/⌬ or mid1⌬/⌬ mouse models displayed attenuated virulence (85).…”
Section: The Roles Of Calcium Signaling In Fungal Cell Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Another component of calcium homeostasis that has been recently identified is the Cch1 voltage-gated Ca 2ϩ channel that is required for calcium uptake in C. neoformans and predicted to be in the plasma membrane (44). Strains with cch1 mutations show sensitivity to calcium chelation, like eca1 mutants, but no temperature sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…All these data show that the Ca 2ϩ -permeable channels seem to be more involved in fungal development than in the interaction with host plants, with one marked exception: deletion of mid1 in the phytopathogenic, biotrophic ascomycete Claviceps purpurea resulted in a complete loss of virulence (28), demonstrating the different roles Mid1 may play in some fungi. However, all mid1 and cch1 deletion mutants generated so far have one phenotype in common: the inability to grow under low-calcium (about 100 nM) conditions, indicating that they are part of the high-affinity calcium influx system (HACS) (29,30). Besides HACS, there also exists a low-affinity calcium influx system (LACS), with the Ca 2ϩ channel Fig1 as the main component.…”
mentioning
confidence: 99%